The Russian military intervention in Syria - Geukjian, Ohannes (McGill-Queen's University Press, 2022)
The Russian Military Intervention in Syria examines Russia's foreign policy and attempts to protect its interests in the Middle East and former Soviet territory. Providing historical context and revealing the causes of Russia's use of military power, this book is an authoritative overview of Russia's policy goals and diplomatic handling of the Syrian conflict.